Competency Identification of Salespersons Through Behavioral Event Interviews : Evidence from the Oil Industry - Das, Mukesh Ranjan; Pathak, Pramod; Singh, Saumya (Prabandhan: Indian Journal of Management, 2018)
Competency studies for highly placed professionals have proliferated across the planet. However, published research papers with data to corroborate the predictive validity of identification of competencies for salespeople (the first link with the customer) is unexplored. Post deregulation onset of cut-throat competition in the oil industry of India makes a compelling case of such research. This paper aimed to identify the differentiating competency set for salespeople manning petrol pumps (retail outlets) using behavioral event interviews (BEIs). BEIs were conducted with 57 salespersons comprising 22 star and 35 average performers of best-performing retail outlets of fossil fuels of a fortune 500 company in Eastern Part of India during May 2015 - June 2016. Eight competencies were distilled from interviews and then sent to 15 industry experts for ranking these competencies independently. The concordance among 12 experts was found significant at the 1% level of significance. Ranking of competencies, as found in BEIs as per frequency of their appearance in interviews, and those given by experts were compared. There was an insignificant difference between the two, thus validating the findings of BEIs. Statistical analysis suggested that a set of four competencies comprising courteous behavior, honesty & integrity, service orientation, and punctuality were differentiating competencies for salespersons of oil industry in India. The findings can be leveraged for hiring, training, career progression, and compensating salespersons by the industry. The same methodology can be adopted to identify competencies of any role with high reliability.